PENGISLAMAN ILMU VS PENGILMUAN ISLAM: Studi Model Penerapan Ilmu Integralistik Pada Perguruan Tinggi Keagamaan Islam di Indonesia - Muhammad Zainal Abidin (Direktorat Pondok Pesntren Universitas Islam Indonesia, 2021)
This paper studies about the model of implementation of integration between Islam and science in Islamic Religious Universities in Indonesia. The transformation from State Institute of Islamic Studies (IAIN) to the State University of Islamic Studies needs the strong spirit to combine between religious knowledge and secular sciences. This spirit may be seen at the consideration clause about the policy of determination of division of sciences as found at PMA RI No. 36 Tahun 2009 which mentioned the need of the integration of the sciences performed by religious colleges. This article is the library-based paper that use the standar procedur in scientific writing. As the result of the article that there at least two models of Islamic- science integration. Both are the model of Islamization of knowledge and the scientificazation of Islam. The first one may be accomodated for the general study program that combined with the islamic value, while the other one may be accomodated for the religious studies that combined with new approach in order to more useful to answer the modernity challenges and fit with the mankind need. Both kind of models have the special advantages, only in model of scientifization of Islam more likely hoped to contribute the new original knowledge.